If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2yb = 7 Reorder the terms: 2by + 3x = 7 Solving 2by + 3x = 7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3x' to each side of the equation. 2by + 3x + -3x = 7 + -3x Combine like terms: 3x + -3x = 0 2by + 0 = 7 + -3x 2by = 7 + -3x Divide each side by '2y'. b = 3.5y-1 + -1.5xy-1 Simplifying b = 3.5y-1 + -1.5xy-1 Reorder the terms: b = -1.5xy-1 + 3.5y-1
| 7x+6-3x=-6x-14+x | | 2q-38=3q-86 | | 5x-27=3x+411 | | (b+2)9= | | 0.12y(y-6)+0.04y=0.08y-0.7 | | -4x-15-3x=-64 | | 13-(x+6)=6x-7 | | 5-2(x-1)-2=12 | | 7(3x+1)-(x+5)=-52 | | 9-6x=-15x | | (3x-12)=51 | | -3+2n=-2 | | 0=-8x^10+32x^9-48x^8+32x^7-8x^6 | | 0.5x^5-0.3x= | | (8+x)*m=5m | | 3X-12Y=-1 | | -5(y+7)=5 | | -10=-x+2-2x | | X+7=3x-21 | | 4+-2y=-11+3y | | 12x-3=32x+2 | | 5x-10x+2=-6 | | 2m+2(3m)=102 | | -x+5x+7=8x+36 | | x^2+18x=-401 | | f(x+6)=2x+3 | | (-3)-2-(-10)2= | | -136+9x=85-8x | | 7x-85=2x-5 | | 27=-10n+n | | -3x+(13+5x)=3 | | x^3+20x^2-132x=288 |